HUBUNGAN KAPASITAS APARATUR DENGAN PEWUJUDAN GOOD GOVERNANCE - Yunus Yunus (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2017)
After the reform movement of 1998, a paradigm shift that developed in the implementation of government in Indonesia. The demands of public administration services are better than ever, become a necessity that would have to be met by government agencies public service providers. The suit appears along with the development of the reform era and regional autonomy and since the fall of the New Order regime. One form of governance (good governance) is the presence of the image of a democratic government. Good governance paradigm emphasizes the importance of the parallel relationship between the institutions of the state, the market and society. Making professional personnel in order to demonstrate the capacity, as well as the identity of the hidden potential that exists in each apparatus be food for thought that is important in the development of human resources, especially in local government at this time.